Methods to apply a Rapid Appraisal of Agricultural Innovation Systems under AE - Ouerghemmi, Hassen; Frija, Aymen; Rejeb, Hichem (International Center for Agricultural Research in the Dry Areas, 2023)
The agricultural innovation system is an approach that consider agricultural innovation from a global perspective. Rapid Appraisal of Agricultural Innovation Systems is one of commonly used methods, it involves series of structured and participatory activities, including interviews, focus group discussions, and stakeholder workshops, to identify the actors, institutions, and relationships involved in the AIS, as well as the strengths and weaknesses of the system. This approach is designed to be flexible and adaptable to local contexts, and it can be used by a range of stakeholders, including development practitioners, policymakers, and researchers. Adapting it to AE transition assessment need a reflection on the concept (What to know) and the requirement (What to get) aiming to suggest as set of feasible analysis that can generate realistic evidence. This Poster occurred during the 20th International Scientific Day of INRGREF in Tunis, Tunisia “Sustainable Ecosystem Management for Agroecological Transition and Food Security” (10-11 October 2023).